PERKARA GUGAT CERAI PADA PENGADILAN AGAMA SORONG - F.A Satria Putra (Muadalah : Jurnal Hukum, 2021)
Every couple wants unity in building a household, but the reality shows that the divorce rate is increasing. Now in some circles of society marriage is no longer considered a sacred social institution so that when a problem or dispute occurs, divorce is immediately an option. This study discusses "the Case for Divorce at the Sorong Religious Court". This type of research is a qualitative research with data collection methods using interviews, observation, and documentation. The causes of divorce consist of adultery, drunkards, drug addicts, gamblers, leaving one of the parties for 2 years, one party getting a prison sentence of more than 5 years, domestic violence, getting a disability or illness which consequently can not run obligations as a wife or husband, continuous disputes and quarrels, violating the word divorce, one of the parties apostates. In this study, the authors conclude that the cause of divorce is only used as a formal requirement in carrying out a lawsuit, because the root cause of divorce is disputes and quarrels that always occur and this cause is the cause that dominates divorce problems at the Sorong Religious Court.